Respostas morfofisiológicas durante o crescimento e produção em genótipo de Crambe sob déficit hídrico - Braga, Priscila da Conceição de Souza (2019)
Crambe (Crambe abyssinica Hochst, Brassicaceae) is an annual crop native to the Mediterranean region of Ethiopia and it has been cultivated in some tropical and subtropical regions. Because it does not compete with oilseeds used in human consumption, it has been an innovative crop in the Brazilian agribusiness sector with a potential supply of insulating vegetable oil. Currently, new genotypes have been tested in order to expand and improve crop productivity in Brazil. The aim of this study was to evaluate the tolerance of crambe genotypes to water deficit in terms of physiological, anatomical and, production aspects in the different development phases. The results obtained will contribute to the crop expansion to regions characterized by low precipitation, such as the State of Espírito Santo. Four experiments were installed: Chapter 1 – this experiment was carried out in a growth room and compare the germination and initial growth of five crambe genotypes (FMS Brilhante, FMS CR 1203, 1307, 1312 and, 1326) submitted to the water deficit induced by polyethylene glycol solution. In this experiment, the germination and vigor index of crambe seeds were hampered by the reduction in the potential to -0.4 MPa. The genotype FMS CR 1203 is the most tolerant to water stress, whereas FMS CR 1307 and 1312 are the most sensitive. Chapter 2 – this experiment was carried out in a greenhouse, investigated and compared the effects of water deficit on vegetative growth on photosynthetic characteristics using kinetic analysis of transient chlorophyll a fluorescence in two crambe genotypes: FMS CR 1307 and 1326. Under water deficit, the crambe genotypes showed differentiated photochemical responses. The FMS CR 1326 genotype presented greater advantage in terms of stability and energy efficiency under water suppression, whereas the FMS CR 1307 genotype appears to have higher PSI photoprotection. Chapter 3 - this experiment was carried out in a greenhouse and evaluated the performance of crambe (FMS Brilhante, FMS CR 1307 and, 1326) under water limiting conditions by previous exposures to water deficit. The repeated exposures to the water deficit in the crambe plants resulted in morpho-physiological changes of the plants, reflecting in a better photochemical performance coupled with moderate anatomical adjustments, indicating differential acclimation (memory to the water deficit) under water deficit. The FMS CR 1307 genotype presented better photochemical performance, confirming the existence of water deficit memory in PSII. Chapter 4 - this experiment was carried out in a greenhouse and investigated the effect of the intense water deficit applied at the beginning of the flowering stage on the physiological characteristics and production of crambe grains (FMS CR 1307 and FMS CR 1326) as well as possible dormancy of the progeny seeds due to water deficit. The water deficit resulted in negative effects on the photochemical apparatus of 11 plants, as well as reductions in stomatal conductance. Furthermore, these changes in the physiological responses of crambe plants reflected reduced grain yield and inhibition in germination the progeny. The FMS CR 1307 genotype presented better photochemical adjustment during the period of water deficit and recovery, confirming photochemical tolerance under water deficit. In view of these results, it is possible to conclude in general that the physiological and anatomical changes contributed positively for the FMS CR 1307 genotype to present greater tolerance to water deficiency in the treatments tested.